Orthogonal Chirp-Division Multiplexing for Future Converged Optical/Millimeter-Wave Radio Access Networks - Colm Browning; Devika Dass; Paul Townsend; Xing Ouyang (IEEE Access, 2022)
Envisaged network scaling in the beyond 5G and 6G era makes the optical transport of high bandwidth radio signals a critical aspect for future radio access networks (RANs), while the move toward wireless transmission in millimeter-wave (mm-wave) and terahertz (THz) environments is pushing a departure from the currently deployed orthogonal frequency division multiplexing (OFDM) modulation scheme. In this work, the orthogonal chirp-division multiplexing (OCDM) waveform is experimentally deployed in a converged optical/mm-wave transmission system comprising 10 km analog radio-over-fiber (A-RoF) transmission, remote mm-wave generation and 2 m wireless transmission at 60 GHz. System performance is evaluated in terms of both bit error ratio (BER) and error vector magnitude (EVM) for a wideband 4 GHz 16 Gb/s signal and 128/256-Quadrature Amplitude Modulation (QAM) mobile signals compatible with 5G new radio numerology. OCDM is shown to outperform OFDM by offering enhanced robustness to channel frequency selectivity, enabling performances below the forward error correction (FEC) limit in all cases and exhibiting an EVM as low as 3.4% in the case of the mobile signal transmission.